The Forgotten - Joseph Ruben; Anthony, Edwards; Christopher Kovaleski; Gary Sinise; Jessica Hecht; Linus Roache; Matthew Pleszewicz; Julianne Moore (USA Revolution Studios, 2004)
A grieving mother, Telly Paretta, is struggling to cope with the loss of her 9-year-old son. She is stunned when her psychiatrist and her husband tell her that she has created eight years of memories of a son she never had. But when she meets the father of one of her son's friend who is having the same experience, Telly embarks on a mission to prove her son's existence and her sanity.
Told that their children never existed, a man and woman soon discover that there's a much bigger enemy at work.
Gerald Di Pego
Language: English Subtitles: English, Turkish, German, French, Spanish, Italian
Keywords: Mystery; SciFi; Thriller; Drama